Potential usefulness of enamel matrix derivative in skin and mucosal injury treatment - Klewin-Steinböck, Sylwia; Adamski, Zygmunt; Wyganowska-Świątkowska, Marzena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Enamel matrix proteins (EMP) are secreted by ameloblasts during odontogenesis. The main component of enamel protein extract is amelogenin. The extracts also contain proteins with bioactive properties similar to bone morphogenic proteins and transforming growth factor 1. Research on animal models indicates that EMP improve healing of oral mucosa wounds by stimulating the production of collagen fibers and blood vessels in the connective tissue. Success in the treatment of oral wounds prompted interest in possible applications of amelogenins in the repair of damaged skin due to similarities in histological structure between skin and mucosa.